2014
DOI: 10.1165/rcmb.2013-0198oc
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 Suppresses Pulmonary Artery Smooth Muscle Cell Proliferation through Inhibition of the STAT3/Pim-1/NFAT Pathway

Abstract: The orphan nuclear receptor 4A (NR4A) family plays critical roles in the regulation of cell proliferation, differentiation, and survival in the cardiovascular system. However, the molecular mechanisms underlying the regulation of NR4A receptor expression and its role in pulmonary artery smooth muscle cell (PASMC) function remain unclear. Here, we investigated whether the NR4A family regulates PASMC proliferation, and if so, which mechanisms are involved. By using quantitative real-time RT-PCR, we showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 48 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…[8][9][10] In VSMCs, Nur77 can be induced by multiple stimuli, including cytokines, growth factors, oxidized low-density lipoprotein, and vascular injury. 11,25,26 We found that Nur77 was highly expressed in medial VSMCs of thoracic aortas from Ang II-infused mice in vivo and in cultured VSMCs after Ang II stimulation in vitro. Several signaling pathways and transcription factors, including MAPK and nuclear factor-κB signaling pathways and MEF-2, AP-1, and CREB, have been reported to regulate the expression of Nur77 in various cell types.…”
Section: Discussionmentioning
confidence: 85%
“…[8][9][10] In VSMCs, Nur77 can be induced by multiple stimuli, including cytokines, growth factors, oxidized low-density lipoprotein, and vascular injury. 11,25,26 We found that Nur77 was highly expressed in medial VSMCs of thoracic aortas from Ang II-infused mice in vivo and in cultured VSMCs after Ang II stimulation in vitro. Several signaling pathways and transcription factors, including MAPK and nuclear factor-κB signaling pathways and MEF-2, AP-1, and CREB, have been reported to regulate the expression of Nur77 in various cell types.…”
Section: Discussionmentioning
confidence: 85%
“…However, Nur77-deficient mice do not show any obvious T cell phenotype (16). A recent study showed that Nur77 inhibits airway smooth muscle cell proliferation in vitro, but this study lacks in vivo data (28). To assess whether Nur77 similarly as in the vessel wall inhibits airway smooth muscle cell proliferation, chronic allergic experiments need to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, peripheral eosinophils from patients with atopic dermatitis show increased Nur77 expression (26). Limited information is available on Nur77 in the lung, but its expression has been described in lung epithelial cells, and a recent study demonstrated that Nur77 inhibits pulmonary smooth muscle cell proliferation (27,28).…”
mentioning
confidence: 99%
“…Knockdown of Nur77 expression was performed by using Nur77 siRNAs, with AllStars negative siRNAs (QIAGEN, Valencia, CA) as a control, as described previously [28]. 2 hrs after seeded into the 6 well plates, cells were transfected using HiPerFect Transfection Reagent (QIAGEN, Valencia, CA) according to the manufacture's protocol.…”
Section: Methodsmentioning
confidence: 99%